CONTACTLESS SERVICES IN VIETNAM'S HOSPITALITY INDUSTRY: CASE STUDIES OF THE JW MARRIOTT HANOI AND THE NOVOTEL HANOI THAI HA HOTEL - Dung, Nguyen Ngoc; Thang, Vu Chien (VNU Journal of Foreign Studies, 2022)
In Vietnam, contactless services in the hotel business are still relatively new. We provide an overview of the research on contactless services and related matters in this study. Following the fishbone or cause and effect diagram first introduced by Kaoru Ishikawa in 1968, the theoretical framework was developed on the five hotel internal factors (5M) that influence the implementation of contactless services in Vietnamese hotels. Our research is grounded in this theoretical framework to investigate the actual condition of providing contactless services at two 5-star hotels, the JW Marriott Hanoi and the Novotel Hanoi Thai Ha. To accomplish the purpose of the research, we used a variety of methodologies, including desk study and analysis; participant observation; questionnaire surveys; and in-depth interviews. Based on the findings of the research, the paper provides discussions and recommendations for the deployment of contactless services in Vietnamese hotels.